( | 5 | x | + | 4 | ) | ( | 6 | x | − | 7 | ) | = | 0 |
Left side of the equation = | 5 | x | ( | 6 | x | − | 7 | ) | + | 4 | ( | 6 | x | − | 7 | ) |
= | 5 | x | × | 6 | x | − | 5 | x | × | 7 | + | 4 | ( | 6 | x | − | 7 | ) |
= | 30 | x | x | − | 35 | x | + | 4 | ( | 6 | x | − | 7 | ) |
= | 30 | x | x | − | 35 | x | + | 4 | × | 6 | x | − | 4 | × | 7 |
= | 30 | x | x | − | 35 | x | + | 24 | x | − | 28 |
= | 30 | x | x | − | 11 | x | − | 28 |
30 | x | x | − | 11 | x | − | 28 | = | 0 |
x1= | - | 4 5 |
x2= | 7 6 |